Adivinación Insospechosa - Monge-Madriz, Carlos (My University, 2021)
El material audiovisual contiene un truco de magia en el cual una persona elije un número del uno al nueve, realiza una serie de pasos que luego le permiten al mago adivinar un país y un animal que el participante pensó. Al final del video se presenta la explicación matemática de la funcionalidad del truco.

The audiovisual material contains a magic trick in which a person chooses a number from one to nine, performs a series of steps that then allow the magician to guess a country and an animal that the participant thought of. At the end of the video, the mathematical explanation of the trick's functionality is presented.
Keywords: Magia -- Matemáticas; Matemáticas recreativas; Magia -- Números; Funcionalidad; Aritmética; Magic -- Mathematics; Recreational mathematics; Magic -- Numbers; Functionality; Arithmetic